Fatimid Dynasty: History of Establishment, Development and Destruction - Tumangger, Maruli (Tabayyun : Journal Of Islamic Studies, 2024)
The Fatimid Dynasty is one of the Shia Dynasties in Islamic history. Its power was in the Egyptian area and was one of the dynasties that contributed to the development of the history of Islamic civilization for Muslims to this day. One of them is Al-Azhar University, Cairo, Egypt. It is interesting to examine how the Fathimiyah Dynasty began to stand firmly, experienced development and progress and until its destruction, at that time the Abbasid Dynasty which was the Islamic caliphate of the superpower at that time was still standing and had not collapsed. This paper will examine the History of the Fathimid Dynasty from a historical perspective.